Behavioral aspect of Wilson Disease: Diagnostic & Management Challenge (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Wilson disease (WD) is a multisystem disease of defective copper metabolism. Excess copper is accumulated in different organ of body including liver, brain, kidney, eyes etc. Accumulated copper causes dysfunction of different parts of brain and produce signs and symptoms of neurological disease. Epidemiological data suggested psychiatric symptoms may be the presenting problem in 30% of WD patients. Psychiatric symptoms developed almost 100% cases of WD patients at any time of the disease course. Psychiatrc symptoms are affective mood disorder, psychotic behavioral, personality changes, anxiety & depression as well cognitive deterioration. Common neurologic symptoms are dystonia, hypertonia & rigidity, tremors and dysarthria. Rarely patients may present with polyneuropathy or dysautonomia. So both neurologic and psychiatric evaluation and specific treatment is essential for both the conditions. Diagnostic evaluations of Wilson disease include estimation of serum ceruloplasmin, 24 hours urinary copper, MRI of brain. Magnetic resonance (MR) imaging of the brain or computed tomography (CT) may detect structures involved like basal ganglia. Knowledge of behavioral problem of WD is helpful for early diagnosis of many cases and overall management. Mainstay of treatment of Wilson disease is dietary restriction of copper-rich diet, copper-chelating agents, symptomatic treatment for dystonia & rigidity as well as behavioral psychiatric therapy. For dystonia trihexy phenidyl, tetrabenazine, codopa & clonidine can be used. Neurologic as well as psychiatric symptoms would be reduced where chelation therapy is effective. More over sometimes pharmacologic treatment for psychiatric symptoms is required.J Bangladesh Coll Phys Surg 2022; 40: 121-127